Dinosaur track assemblages from mid-Cretaceous of Fujian Province, southeastern China: ichnotaxonomic review and faunal comparison - Xing,Lida; Niu,Kecheng; Chen,Qiyan; Klein,Hendrik; Romilio,Anthony; Chen,Runsheng; Lin,Min; Deng,Ke; Tang,Jianrong (PeerJ, 2025)
Among the the mid-Cretaceous strata in China, considerable dinosaur record are preserved in the southeastern mountainous and arc-related basins. The Shanghang Basin is one of the sporadic red-stratified basins distributed in western Fujian, SE China, and has previously been discovered as the home of an ornithopod-dominaited ichnofauna, which is also characterized by the large troodontid ichnogenera Fujianipus. Include the newly discovered fossils, further confirming that this tracksite is dominated by ornithopods, characterized by a significant proportion (>27%) of large ornithopods, with deinonychosaurians as the possible apex predators. As the only extensive mid-Cretaceous dinosaur tracksite in southeastern China, Longxing offers a temporal comparison with skeletal records from Zhejiang (SE China) and other fauna globally. The Longxiang herbivorous assemblage may suggesting limited faunal turnover by aligning more closely with pre-Cenomanian than the contemporaneous faunas in Zhejiang. Besides, unlike South American patterns associated with OAE2, the faunal shifts of SE China are relatively mild and appear more influenced by regional factors—topographic barriers and volcanic activities—rather than global climatic signal affected by marine conditions. Further research is needed to refine faunal chronology and assess the impact of regional environmental factors in shaping Cretaceous ecosystems of SE China.
Keywords: Brontopodus; Caririchnium; Didactcyl track; Shaxian Formation; Early Late Cretaceous; Ichnotaxonomy; Ichnofauna; East Asia